PSYCHOLINGUISTICS AND ITS FEATURES (Web of Teachers: Inderscience Research, 2024)
This article explores the key features of psycholinguistics, focusing on the cognitive and neural mechanisms involved in language processing, the role of syntax and semantics in sentence comprehension, and the influence of cognitive load on language production. It also investigates lexical access and word recognition through priming studies, and highlights the role of bilingualism in shaping cognitive flexibility and language processing. The paper further discusses language acquisition, the influence of social interaction, and the brain regions associated with language function. Drawing from experimental methods such as reaction time studies, eye-tracking, ERP, and neuroimaging, the article provides a comprehensive overview of current research trends in psycholinguistics. The findings offer valuable insights into the dynamic interaction between cognitive systems and language, advancing our understanding of how humans process and use language in real-world contexts.